2016
DOI: 10.1103/physrevb.93.161411
|View full text |Cite
|
Sign up to set email alerts
|

Theory of third-harmonic generation in graphene: A diagrammatic approach

Abstract: We present a finite-temperature diagrammatic perturbation theory of third harmonic generation (THG) in doped graphene. We carry out calculations of the third-order conductivity in the scalar potential gauge, highlighting a subtle cancellation between a Fermi surface contribution, which contains only power laws, and power-law contributions of inter-band nature. Only logarithms survive in the final result. We conclude by presenting quantitative results for the up-conversion efficiency at zero and finite temperat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 26 publications
4
91
0
Order By: Relevance
“…The third‐order susceptibility χ (3) is a complex number. Its imaginary part describes triple‐frequency phenomenon, including nonlinear absorption, third‐harmonic generation, parametric process, and Raman effect, while its real part describes the Kerr nonlinearity.…”
Section: Fundamental Of 2d Layered Materialsmentioning
confidence: 99%
“…The third‐order susceptibility χ (3) is a complex number. Its imaginary part describes triple‐frequency phenomenon, including nonlinear absorption, third‐harmonic generation, parametric process, and Raman effect, while its real part describes the Kerr nonlinearity.…”
Section: Fundamental Of 2d Layered Materialsmentioning
confidence: 99%
“…The peaks predicted in [3,4,7] emerges at lower temperature (T 10 −2 µ). Under transition to the normal state the double peak at ω ≈ (2/3) µ 2 + ∆ 2 is transformed to the peak at ω = (2/3)µ, and the peaks at ω = (2/3)∆, ω = ∆, and ω = 2∆ disappear.…”
Section: P-2 Enhancement Of Third Harmonic Generation Caused By Electmentioning
confidence: 99%
“…This equation yields the electric current that contains all odd Fourier harmonics with the amplitudes falling down very slowly with the harmonic number. The quantum approach [3][4][5][6][7] predicts resonant behavior for the third harmonic generation in graphene. The frequency dependence of the THG intensity has the main peak at ω = (2/3)ε F and two minor peaks at ω = ε F and ω = 2ε F , where ε F is the Fermi energy.…”
mentioning
confidence: 99%
“…The series of studies on graphene's numerous nonlinear optical processes, as shown in figure 7, can be traced back to contributions by Mikhailov since 2007 [58][59][60][61][62][63] [78][79][80] and more recently by other groups [81][82][83][84][85][86][87][88][89].…”
Section: Nonlinear Optical Properties Of Graphene (A) Theoretical Stumentioning
confidence: 99%
“…Perturbative models are developed to supplement the interband physics, for example the quantum mechanical (QM) Dirac equation model [61,62,64,66,67,89], and also the semiconductor Bloch equations [73,75,76,85]. The QM model replaces v g in equation (3.1) with v g = ψ|∂ H/∂k|ψ , where ψ is the wave function of graphene and H is the Dirac Hamiltonian, which replaces N(p) with N(p) = f (−ε k ) − f (ε k ), the Fermi distribution difference between the conduction and valence bands.…”
Section: Nonlinear Optical Properties Of Graphene (A) Theoretical Stumentioning
confidence: 99%